In vitro profiling of toxic effects of prominent environmental lower-chlorinated PCB congeners linked with endocrine disruption and tumor promotion - Pěnčíková, Kateřina; Svržková, Lucie; Strapáčová, Simona; Neča, Jiří; Bartoňková, Iveta; Dvořák, Zdeněk; Hýžďalová, Martina; Pivnička, Jakub; Pálková, Lenka; Lehmler, Hans-Joachim; Li, Xueshu; Vondráček, Jan; et al. (Environmental pollution (Barking, Essex, 2018)
The mechanisms contributing to toxic effects of airborne lower-chlorinated PCB congeners (LC-PCBs) remain poorly characterized. We evaluated in vitro toxicities of environmental LC-PCBs found in both indoor and outdoor air (PCB 4, 8, 11, 18, 28 and 31), and selected hydroxylated metabolites of PCB 8, 11 and 18, using reporter gene assays, as well as other functional cellular bioassays. We focused on processes linked with endocrine disruption, tumor promotion and/or regulation of transcription factors controlling metabolism of both endogenous compounds and xenobiotics. The tested LC-PCBs were found to be mostly efficient anti-androgenic (within nanomolar - micromolar range) and estrogenic (at micromolar concentrations) compounds, as well as inhibitors of gap junctional intercellular communication (GJIC) at micromolar concentrations. PCB 8, 28 and 31 were found to partially inhibit the aryl hydrocarbon receptor (AhR)-mediated activity. The tested LC-PCBs were also partial constitutive androstane receptor (CAR) and pregnane X receptor (PXR) agonists, with PCB 4, 8 and 18 being the most active compounds. They were inactive towards other nuclear receptors, such as vitamin D receptor, thyroid receptor α, glucocorticoid receptor or peroxisome proliferator-activated receptor γ. We found that only PCB 8 contributed to generation of oxidative stress, while all tested LC-PCBs induced arachidonic acid release (albeit without further modulations of arachidonic acid metabolism) in human lung epithelial cells. Importantly, estrogenic effects of hydroxylated (OH-PCB) metabolites of LC-PCBs (4-OH-PCB 8, 4-OH-PCB 11 and 4'-OH-PCB 18) were higher than those of the parent PCBs, while their other toxic effects were only slightly altered or suppressed. This suggested that metabolism may alter toxicity profiles of LC-PCBs in a receptor-specific manner. In summary, anti-androgenic and estrogenic activities, acute inhibition of GJIC and suppression of the AhR-mediated activity were found to be the most relevant modes of action of airborne LC-PCBs, although they partially affected also additional cellular targets.
Keywords: Endocrine Disruptors; Cell Line; HydroxyLated PCBs; polychlorované bifenyly; epitelové buňky; Hydroxylation; Neoplasms; steroidní receptory; Receptors, Cytoplasmic and Nuclear; hydroxylace; Epithelial Cells; signální transdukce; Airborne polychlorinated biphenyls; Polychlorinated Biphenyls; Signal Transduction; látky znečišťující vzduch; Tumor promotion; endokrinní disruptory; pregnanový X receptor; lidé; konstitutivní androstanový receptor; Receptors, Steroid; Metabolism of xenobiotics; Humans; buněčné linie; nádory; receptory cytoplazmatické a nukleární; Endocrine disruption; Pregnane X Receptor; Constitutive Androstane Receptor; Air Pollutants